(untitled) (Collection of scientific works «Modern structures of metal and wood», 2021)
Cold rolled steel structures have been known since the mid-19th century in the United States and Great Britain. Despite the advances in the development of cold-rolled structures, the level of their use was lower than that of hot-rolled structures. A significant factor that influenced this imbalance in application was the fact that there were no regulations. Into different countries of the world have their own national regulations for the calculation of cold-rolled steel structures, which have many controversies. In the European group includes the norms of the countries of the European Union, Great Britain, Hong Kong, Ukraine, Belarus, Kazakhstan; American group - the United States of America, Canada, Mexico, Australia, New Zealand, Brazil, Chile, Egypt. The regulations of such large countries as China, India and Russia have their own characteristics. The article presents the results of a technical survey of the load-bearing structures of the canopy. The survey was carried out to determine the bearing capacity of the roof load-bearing structures in relation to the location of the solar panels on the roof of the building. The construction of buildings and their structural parts from light steel thin-walled structures (profiles) is carried out in the form of light frames, the frames of which are successively connected into spatial systems. A new lightweight roof covering made of profiled sheet and a frame structure made of cold-rolled P-profile and C-profile elements for roofing and installation of solar panels are proposed. Such a coating is the most industrialized, easily and quickly erected. The analysis of constructive options for the effective placement of the profile of cold-rolled elements and joints of the frame and reinforced concrete run of the coating is carried out. The design of the frame was carried out in the software package " Лира САПР 2013" . The results of the work carried out served to draw up recommendations for restoring the properties of the load-bearing structures of the canopy, the development of design estimates and implementations into construction practice during the reconstruction of the canopy.